2009
DOI: 10.1074/jbc.m109.051839
|View full text |Cite
|
Sign up to set email alerts
|

The Fifth Transmembrane Domain of Angiotensin II Type 1 Receptor Participates in the Formation of the Ligand-binding Pocket and Undergoes a Counterclockwise Rotation upon Receptor Activation

Abstract: The octapeptide hormone angiotensin II exerts a wide variety of cardiovascular effects through the activation of the angiotensin II Type 1 (AT 1 ) receptor, which belongs to the G protein-coupled receptor superfamily. Like other G proteincoupled receptors, the AT 1 receptor possesses seven transmembrane domains that provide structural support for the formation of the ligand-binding pocket. The role of the fifth transmembrane domain (TMD5) was investigated using the substituted cysteine accessibility method. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Likewise, it was reported that treatment of COS-1 cells expressing human cannabinoid receptor (CB1) with MMTS or MTSEA leads to a dramatic reduction in agonist SR141716A binding to the receptor; such treatment, however, had no significant effect on agonist CP55940 binding to the CB1 receptor (69). Human AT 1 receptors (70) and P2X 2 (61) are shown to be insensitive to MTSEA and MTSET, respectively. On the other hand, it was reported that MTSET treatment of HEK cells transiently overexpressing glucagon receptor enhanced (instead of decreasing) glucagon potency for cAMP stimulation by two- to three-fold (71).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, it was reported that treatment of COS-1 cells expressing human cannabinoid receptor (CB1) with MMTS or MTSEA leads to a dramatic reduction in agonist SR141716A binding to the receptor; such treatment, however, had no significant effect on agonist CP55940 binding to the CB1 receptor (69). Human AT 1 receptors (70) and P2X 2 (61) are shown to be insensitive to MTSEA and MTSET, respectively. On the other hand, it was reported that MTSET treatment of HEK cells transiently overexpressing glucagon receptor enhanced (instead of decreasing) glucagon potency for cAMP stimulation by two- to three-fold (71).…”
Section: Discussionmentioning
confidence: 99%
“…Previous AT1R structure-function studies have suggested both rotational and translational motion of TM2, TM3, TM5, TM6 and TM7 in the constitutively active mutant N111G-AT1R, which mimics the active state of AT1R [5962]. In the active state, formation of the Asn46-Asp74-Asn295 H-bond network is proposed, which involves additional interacting residues around Asn111 TM3 and Asn295 TM7 (see Section 5).…”
Section: Mechanism Of Decreased Maximal Inverse Agonist Activity Omentioning
confidence: 94%
“…The basal activity of N111G-AT1R can be inhibited by AT1R-selective blockers, albeit at 3-315-fold higher concentrations compared with wild-type AT1R (16,19,20,22,23). The conformation of the TMD of the N111G-AT1R has been shown to be altered to the activated state (12,13,(32)(33)(34)(35)(36). The RCAM results in Fig.…”
Section: At1r and D281a-cysmentioning
confidence: 95%